11beta-Hydroxysteroid dehydrogenase type 1 regulates insulin and glucagon secretion in pancreatic islets. - Swali, A; Walker, E; Lavery, G; Tomlinson, J; Stewart, P (2008)
AIMS/HYPOTHESIS: Exposure to excess glucocorticoid is associated with pancreatic beta cell damage and decreased glucose-stimulated insulin secretion (GSIS). Inactive glucocorticoids (cortisone, 11-dehydrocorticosterone) are converted to active cortisol and corticosterone by 11beta-hydroxysteroid dehydrogenase type 1 (11beta-HSD1), which requires NADPH as cofactor, which is generated by hexose-6-phosphate dehydrogenase (H6PDH). We investigated the localisation and activity of 11beta-HSD1 within pancreatic islets, and determined its functional role in the regulation of insulin and glucagon secretion. METHODS: mRNA expression of 11beta-HSD1 (also known as HSD11B1), glucocorticoid receptor and H6PDH (also known as H6PD) in human pancreas and murine islets was examined by real-time PCR. 11beta-HSD1 protein levels were examined by immunohistochemistry and immunofluorescence. 11beta-HSD1 activity was assessed in intact tissue and isolated islets of wild-type (WT) and both 11beta-Hsd1- and H6pdh-null mice. Glucagon secretion and insulin secretion were analysed by RIA and ELISA respectively in isolated murine islets incubated with dexamethasone. RESULTS: 11beta-HSD1 co-localised with glucagon in the periphery of murine and human islets, but not with insulin or somatostatin. Dexamethasone, 11-dehydrocorticosterone and corticosterone induced a dose-dependent decrease in GSIS and glucagon secretion following low glucose stimulation. Reduction of 11beta-HSD1 activity with specific inhibitors or in experiments carried out in H6pdh-null mice reversed the effects of 11-dehydrocorticosterone, but had no effect following treatment with corticosterone. CONCLUSIONS/INTERPRETATION: Local regeneration of glucocorticoid via 11beta-HSD1 within alpha cells regulates glucagon secretion and in addition may act in a paracrine manner to limit insulin secretion from beta cells.